Avery Rush: capstone - Rush, Avery, artist (Colorado State University. Libraries, 2023)
The artist's statement: In my artistic practice, I explore the delicate balance between beauty and grotesqueness. My fascination with the unusual, mysterious, and spooky has been a constant throughout my life. By embracing objects, materials, and imagery that are often associated with negative connotations, I have been able to evoke a sense of empowerment through body adornment. My artwork not only allows me to express myself creatively but also enables me to gain a deeper understanding of my relationship with the world around me. By confronting and accepting the parts of myself that I have previously deemed unworthy or shameful, I am able to heal the inner wounds that have been inflicted upon me. My creations serve as a representation of acceptance and self-love. Through my art, I have learned the importance of sitting with uncomfortable emotions and experiences, allowing myself to fully feel and understand them. This practice has taught me to be comfortable with all aspects of myself, both positive and negative. As I continue to produce new works, I am empowered to be my most authentic self and to share my unique perspective with the world.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: metalsmithing